Empirical Research for Information Professionals - Liu, Yan Quan (Information and library service studies, 2019)
A collection of empirical research published by Dr. yan Quan Liu and his reasearch teams in the field of information and library science for the 21st-century readers. - Back cover.
Keywords: Case studies; Library science; Research; Library science; dept.ils; faculty_collection